Towards sub-0.5 A electron beams. - Krivanek, O; Nellist, P; Dellby, N; Murfitt, M; Szilagyi, Z (2003)
In the 4 years since the previous meeting in the SALSA series, aberration correction has progressed from a promising concept to a powerful research tool. We summarize the factors that have enabled 100-120kV scanning transmission electron microscopes to achieve sub-A resolution, and to increase the current available in an atom-sized probe by a factor of 10 and more. Once C(s) is corrected, fifth-order spherical aberration (C(5)) and chromatic aberration (C(c)) pose new limits on resolution. We describe a quadrupole/octupole corrector of a new design, which will correct all fifth-order aberrations while introducing less than 0.2mm of additional C(c). Coupled to an optimized STEM column, the new corrector promises to lead to routine sub-A electron probes at 100kV, and to sub-0.5A probes at higher operating voltages.